An NIR‐II Absorbing Injectable Hydrogel for Boosted Photo‐Immunotherapy Toward Human Papillomavirus Associated Cancer - Xinghua Yu; Lingan Zeng; Xinyue Yang; Zuliang Ren; Xuemei Dong; Ge Meng; Guogang Shan; Dingyuan Yan; Dong Wang; Fei Sun (Aggregate)
ABSTRACT Human papillomavirus (HPV) is a highly prevalent venereal pathogen accounting for genital warts and various cancers like cervical, anal, and oropharyngeal cancers. Although imiquimod, a topical medication, is commonly used to treat genital warts induced by HPV, its potential as an in situ immune response regulator for HPV‐related cancers has rarely been explored. In this study, we developed an innovative synergistic therapeutic platform by integrating near‐infrared‐II (NIR‐II) absorbing aggregation‐induced emission (AIE) agent (TPE‐BT‐BBTD) and imiquimod into an injectable hydrogel named TIH. TPE‐BT‐BBTD molecule that serves as a photothermal agent, with exposure to a 1064 nm laser, effectively destroys tumor cells and releases tumor‐related antigens. During the thermogenesis process, the hydrogel melts and releases imiquimod. The released imiquimod, in conjunction with the dead tumor antigens, stimulates dendritic cell maturation, activating the immune system to ultimately eliminate residual cancer cells. This novel approach combines the immunomodulatory effects of imiquimod with a 1064 nm‐excitable photothermal agent in a hydrogel delivery system, offering a promising tactic for combating HPV‐associated cancers.